Modelling of complex fractal objects for aesthetic product development. (20th February 2007) - Li, C.L.; Yeung, Y.C.; Chiu, W.K.; Yu, K.M.
Fractal geometry has been used for modelling natural objects that cannot be described by Euclidean geometry, and is also employed in aesthetic product design. However, the contemporary Computer-Aided Design (CAD) and Computer-Aided Manufacturing (CAM) systems are well developed only for semi-analytical and free-form objects, and they cannot deal with aesthetic appealing objects efficiently. As a result, new data structure or representation model has to be introduced in order to model and process the fractal geometry effectively in Euclidean-based CAD/CAM system. In this paper an algorithm is proposed for generating a 3D complex fractal from its mathematical models. To represent the 3D complex fractal object model in a CAD system, a voxel-based model is introduced. To fabricate a physical fractal object, Layered Manufacturing (LM) technology is employed. The geometrical information of the fractal object is extracted from its voxel-based model and the LM tool path can be generated accordingly. Applying the proposed algorithm, the fabrication of a fractal object can be realised.